Predictors of CT-derived FFR in patients with suspected CAD beyond severity of coronary stenosis. (14th October 2021) - Smolka, S; Fava, A; Moshage, M; Marwan, M; Achenbach, S; Desai, M Y
Abstract: Background: Functional assessment of coronary stenosis using computational fluid dynamics is increasingly used, however other factors besides coronary stenosis may affect the results. We assessed several predictors for CT-derived fractional flow reserve (CT-FFR) in patients with suspected coronary artery disease (CAD) undergoing coronary computed tomographic angiography (CCTA). Methods: 2505 consecutive patients with suspected CAD undergoing CCTA from 2008 to 2016 were screened, 1549 were excluded due to incomplete data (934), image quality (345), software error (147) or other reasons (123). Minimal CT-FFR was measured using an on-site prototype (cFFR Version 3.0, Siemens Healthineers, Forchheim, Germany) in coronaries ≥2mm. Several clinical as well as technical criteria were assessed for predicting the minimal CT-FFR per patient. Results: 956 patients (51±12 years, 51.2% men) were included in this analysis. Mean EF was 59.4±7.4%, heart rate 63±9 bpm, systolic (126.5±20mmHg) and diastolic (70±11 mmHg) blood pressure (BP). Regression analysis and ANOVA showed low but significant impact on minimal CT-FFR (mean 0.85±0.10) by EF, aortic valvular dysfunction, heart rate and systolic blood pressure as well as image quality (esp. blooming and image noise). See Tables 1 and 2. Conclusion: Coronary stenosis may not be the only relevant predictor for CT-FFR. Several clinical criteria (EF, heart rate, BP, aortic valve dysfunction) as well as image criteria (image quality, artifacts) can affect CT-FFR results. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Cleveland Clinic Foundation